More Freedom, Less Terror? - Kaye, Dalia Dassa; Wehrey, Frederic; Grant, Audra K.; Stahl, Dale (RAND Corporation, 2023)
A key tenet of U.S. foreign policy has been that promoting democracy reduces terrorism; however, scant empirical evidence links democracy to terrorism, positively or negatively. This study explores the relationship between the two by examining the effects of liberalization processes on political violence in six Arab cases.